Novel power generation models integrated supercritical water gasification of coal and parallel partial chemical heat recovery. (1st September 2017) - Chen, Zhewen; Zhang, Xiaosong; Li, Sheng; Gao, Lin
Abstract: Supercritical water gasification (SCWG) of coal is a promising clean coal technology. Supercritical water can effectively and cleanly convert coal to hydrogen-rich syngas. Three power generation models integrated SCWG of coal are proposed and compared in this article. The gasification products have a large amount of sensible heat. Efficient use of the sensible heat can improve the model performance. Compared to the models with total and without chemical heat recovery, the model with partial chemical heat recovery has the advantages of much less exhausted energy and relative small amount of fuel coal used to heat the water to the supercritical state. The efficiency of the model with partial chemical heat recovery is higher than that of other models, and increases with increasing coal-water slurry concentration (CWSC). The efficiencies of the models with partial chemical heat recovery, without chemical heat recovery, and with total chemical heat recovery are 46.60%, 37.56%, and 42.17% when CWSC is 11.3%, respectively. The thermal efficiency of the PCHR model is higher than most conventional coal-fired power plants and coal-based IGCC projects. Highlights: Three novel models integrated SCWG of coal with power generation are proposed, and analyzed. Energetic analyses through energy flow diagrams. Maximum thermal efficiency of 46.60% of all the models is obtained.